Corporate brands and corporate identity : how to position the organisation amongst stakeholders in South Africa - Boyce, Bhekinkosi Isaac (My University, 2017)
Abstract  The current business environment has changed  drastically from  the environment that  was prevalent prior to the turn of the century. Globalisation,  and the introduction of  new technologies, has changed the way business is being conducted and this has  facilitated the development of  new markets. Such disruptions have  meant  that  competitive advantage  is no  longer  sustainable  over   a long period  of  time because  competitors can now easily replicate  one’s  products.  In  an  attempt to  sustain competitive advantage there has been an  introduction of a new  approach  to  marketing in organisations. Organisations are slowly shifting their  approach from product branding to corporate branding.   The aspect of corporate  branding  is a new  concept  that has  gained traction  only as recently as 1995. As a result, less is  known  about how  the  corporate  branding   process  is  initiated  and  conducted  effectively  in order to realise the desired   outcomes. Consequently, a lot of  marketing personnel confuse  the concept  of   corporate branding with product branding which is more commonly  understood   and has  been researched  extensively.   The  main aim of  this study is therefore  to analyse how South African retail   organisations  are  positioning  their  brands  amongst  their  stakeholders.  A  fully  comprehensive  approach to corporate brand building, which seeks to include  all of  the  organisation’s  stakeholders,  is most likely to be  appealing to the   organisation’s stakeholders ensuring a  sustainable competitive advantage.   External stakeholders,  like the  customers, will  be more  than happy to be   associate  with  the corporate brand as it represent the promise that the organisation is pledging.
M.B.A. Thesis
Keywords: Branding (Marketing),Corporate image -- South Africa.